2004
DOI: 10.1023/b:verc.0000017369.04003.2b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drinking-Water Administration of Experimental Chlorate Ion Preparations on Salmonella enterica serovar Typhimurium Colonization in Weaned and Finished Pigs

Abstract: Foodborne disease caused by Salmonella is of public health and economic significance. In order to assess the practical effectiveness of a new intervention strategy, experimental chlorate preparations (ECP) were administered via the drinking water to weaned and finished pigs that had been orally challenged the previous day with 10(9)-10(10) colony-forming units of Salmonella serovar Typhimurium. After 24 or 36 h ad libitum access to 0X, 1X or 2X ECP treatment (where X is the concentration estimated to deliver a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 23 publications
1
18
0
3
Order By: Relevance
“…In addition to the above‐mentioned measures, the sows were fed 30 g/kg feed/sow/day Formyl ® (SODA, Monaco), which is an encapsulated mixture of formiate 66% and citrate 33%. This treatment had the potential to acidify the colon content, resulting in an inhibition of salmonellae reproduction (Fenwick and Olander, 1987; Hojberg et al., 2003; Anderson et al., 2004). The Formyl ® feed was started at day 14 antepartum and ended at weaning.…”
Section: Eradication Measuresmentioning
confidence: 99%
“…In addition to the above‐mentioned measures, the sows were fed 30 g/kg feed/sow/day Formyl ® (SODA, Monaco), which is an encapsulated mixture of formiate 66% and citrate 33%. This treatment had the potential to acidify the colon content, resulting in an inhibition of salmonellae reproduction (Fenwick and Olander, 1987; Hojberg et al., 2003; Anderson et al., 2004). The Formyl ® feed was started at day 14 antepartum and ended at weaning.…”
Section: Eradication Measuresmentioning
confidence: 99%
“…Briefly, unlabeled sodium chlorate (0.1370 g) was weighed (Mettler AE100 balance, Mettler Instrument Corp., Heightstown, NJ), dissolved in water, and transferred to a 100 mL volumetric flask. Triplicate 4,8,12, and 16 µL aliquots of the chlorate solution were injected onto the ion chromatography system, described for the determination of radiochemical purity, and the respective peak areas were recorded. Quadruplicate injections (10 and 25 µL, respectively) of stock and formulated sodium [ 36 Cl]chlorate were made; peak areas were recorded, and the sodium [ 36 Cl]chlorate peaks were trapped into LSC vials and counted for a minimum of 10 min.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, our laboratory has shown that oral administration of ECP significantly reduced Salmonella colonization in the gut of pigs, broilers and turkeys (Anderson et al, 2001a(Anderson et al, ,b, 2004Byrd et al, 2003;Jung et al, 2003;Moore et al, 2006;). Drinking water or feed administration of ECP has also resulted in significant reductions of generic E. coli, E. coli O157:H7, or both in cattle and sheep gut concentrations (Anderson et al, , 2005Callaway et al, 2002Callaway et al, , 2003.…”
Section: Discussionmentioning
confidence: 97%